RAÍZES ARTIFICIAIS: SOLIDÃO, TECNOLOGIA E TOTALITARISMO NA VIDA CONTEMPORÂNEA (ESMAT Magazine, 2024)
In today's society, loneliness has become an evident paradox. Technology connects people globally while simultaneously distancing them, generating a certain existential void. The pact offered by major technology companies promises endless possibilities in exchange for personal data, leading to the exclusion of those who do not adhere to it - an attitude resembling a new form of totalitarianism, less visible but equally controlling. Since the industrial revolution, control over human life has intensified, now exacerbated by the digitalization of relationships and the world. Hannah Arendt's analyses of the roots of totalitarianism, present in this article, serve as a springboard for understanding the relationship between totalitarianism and technology in contemporary society. This work is based on the adoption of a dialectical methodological approach, focusing on the monographic procedural method. Qualitative research technique is employed, supported by bibliographic documentary research.
Keywords: Loneliness; Technology; Digital Totalitarianism; Alienation; Bid Nudge